Optimization design of fuel tank structure for a certain excavator based on finite element analysis - Chen, Bowen; Jiao, Peigang; Qi, Guoqing; Zhang, Yanan (Sound & Vibration, 2026)
This study focuses on the fuel tank of a specific excavator model, employing CATIA for modeling and ANSYS Workbench for finite element analysis. Static strength, modal, and random vibration simulations were performed to address stress concentration, excessive deformation, and resonance risks caused by oil sloshing. An optimized design was proposed and experimentally validated. The original fuel tank was first simplified and modeled using Q235 material. A mesh convergence study determined a 10 mm element size, balancing accuracy and computational efficiency. Static analysis confirmed that maximum stress and deformation met material allowables. Modal analysis revealed a first natural frequency of approximately 67.40 Hz, significantly above the frame's excitation frequency of around 10 Hz, effectively avoiding resonance. Random vibration analysis indicated prominent Y-direction deformation and X-direction stress. An optimization scheme was developed: symmetrically lengthening the transverse anti-slosh baffles and adding rounded stiffening ribs at the bottom. Post-optimization, deformations and stresses decreased markedly in all directions, with X-direction stress reduced by over 60%. Bench strain testing agreed with simulation results to within 91%, verifying the reliability and safety of the optimized structure. Results demonstrate that combining anti-slosh baffles with stiffening ribs significantly enhances vibration resistance, reduces fatigue failure risk, and maintains controllable manufacturing processes and costs. This provides a reusable simulation and optimization methodology for lightweight, durable fuel tank design in construction machinery.